How Well Do Your Provider's Practices Match the Evidence? - Hotelling, Barbara A. (Lamaze International, 2007)
The handout presented in this article can be used by expectant parents to compare the evidence-based, expected occurrence of routine interventions with the usual care given by their chosen provider and place of birth. The known occurrence of these routine interventions is derived from Listening to Mothers II: Report of the Second National U.S. Survey of Women's Childbearing Experiences. The evidence of harm or benefit is derived from both the Cochrane Collaboration and the Coalition for Improving Maternity Services.